Sea-level performance is enhanced by acute intermittent hypobaric hypoxia - Meeuwsen, T.; Hendriksen, I. J. M.; Holewijn, M. (Medicine & Science in Sports & Exercise, 1999)
The effects of intermittent exposure to altitude in a hypobaric chamber on sea level performance were investigated. Two groups of elite male triathletes trained two hours each day for 10 days on a cycle ergometer in a hypobaric chamber simulating 2,500 m altitude (N = 8) or sea level (N = 8). Measurements were taken before and two and nine days after the exposure. Significant increases in the hypoxia group were seen in all parameters of the maximal aerobic and anaerobic tests. VO2max improved by 7% and mean maximal power output per kg body weight increased by 7.4%. Both mean anaerobic capacity and power increased by 5%. Time until peak anaerobic power was reduced by 37.7%. Measures in the sea level group changed in similar but nonsignificant directions. This study shows remarkable changes from a simple experience. It will be interesting to see what eventuates from cross-validation studies performed by other laboratories with different groups of athletes. Implication: Are these results too good to be true?